MIR396-GRF/GIF enhances in planta shoot regeneration of Dendrobium catenatum - Zhenyu Yang; Meili Zhao; Xiaojie Zhang; Lili Gu; Jian Li; Feng Ming; Meina Wang; Zhicai Wang (BMC Genomics, 2024)
Summary Recent studies on co-transformation of the growth regulator, TaGRF4-GIF1 chimera (Growth Regulating Factor 4-GRF Interacting Factor 1), in cultivated wheat varieties (Triticum aestivum), showed improved regeneration efficiency, marking a significant breakthrough. Here, a simple and reproducible protocol using the GRF4-GIF1 chimera was established and tested in the medicinal orchid Dendrobium catenatum, a monocot orchid species. TaGRF4-GIF1 from T. aestivum and DcGRF4-GIF1 from D. catenatum were reconstructed, with the chimeras significantly enhancing the regeneration efficiency of D. catenatum through in planta transformation. Further, mutating the microRNA396 (miR396) target sites in TaGRF4 and DcGRF4 improved regeneration efficiency. The target mimicry version of miR396 (MIM396) not only boosted shoot regeneration but also enhanced plant growth. Our methods revealed a powerful tool for the enhanced regeneration and genetic transformation of D. catenatum.